The Urban Imperative : Toward Shared Prosperity - Glaeser, Edward (World Bank, Washingotn, DC, 2014)
Urbanization is undoubtedly a key driver of development - cities provide the national platform for prosperity, job creation, and poverty reduction. But urbanization also poses enormous challenges that one is familiar with: congestion, air pollution, social divisions, crime, the breakdown of public services and infrastructure, and the slums that one billion urban resident's call home. Urbanization is perhaps the single most important question in development today. It is clear that cities have not performed as well as can be expected in their transformative role for more livable, inclusive, people-centered, and sustainable development. But they have enormous potential as growth escalators, offering the opportunity to lift millions out of poverty, and serve as centers of knowledge, innovations, and entrepreneurship. Cities in both the developed and developing world want to attract more entrepreneurs and create more jobs. Cities also need to be resilient to natural hazards and the impacts of climate change. If these are left unaddressed, cities will become part of the problem rather than the solution.